POLITIK DINASTI DITENGAH SISTEM DEMOKRASI: MENYIMAK ISU REPUBLIK RASA KERAJAAN - Jiddan Gamal Qondas; Sutopo (Program Studi Hukum Tata Negara dan diterbitkan oleh Program Studi Hukum Tata Negara dan Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Sunan Drajat Lamongan, 2024)
Dynastic politics is actually just a term in political science which means the process of directing the regeneration of power for the interests of certain groups with the aim of gaining or maintaining power in a country. In democratic countries, this term often appears, even though in democratic countries, power is in the hands of the people, which is where the term dynastic politics first appeared. is when royal power or absolute monarchy, where power is passed on/inherited from the previous ruler to the next ruler. Indonesia is a country that has a democratic system, namely sovereignty is in the hands of the people, this is in accordance with the preamble to the 1945 Constitution, a fragment of the fourth paragraph which states